Characterization of Genes Encoding Key Enzymes Involved in Anthocyanin Metabolism of Kiwifruit during Storage Period - Li, Boqiang; Xia, Yongxiu; Wang, Yuying; Qin, Guozheng; Tian, Shiping (Frontiers in Plant Science, 2017)
‘Hongyang’ is a red fleshed kiwifruit with high anthocyanin content. In this study, we mainly investigated effects of different temperatures (25 and 0°C) on anthocyanin biosynthesis in harvested kiwifruit, and characterized the genes encoding key enzymes involved in anthocyanin metabolism, as well as evaluated the mode of the action, by which low temperature regulates anthocyanin accumulation in ‘Hongyang’ kiwifruit during storage period. The results showed that low temperature could effectively enhance the anthocyanin accumulation of kiwifruit in the end of storage period (90 days), which related to the increase in mRNA levels of ANS1, ANS2, DRF1, DRF2, and UGFT2. Moreover, the transcript abundance of MYBA1-1 and MYB5-1, the genes encoding an important component of MYB–bHLH–WD40 (MBW) complex, was up-regulated, possibly contributing to the induction of specific anthocyanin biosynthesis genes under the low temperature. To further investigate the roles of AcMYB5-1/5-2/A1-1 in regulation of anthocyanin biosynthesis, genes encoding the three transcription factors were transiently transformed in Nicotiana benthamiana leaves. Overexpression of AcMYB5-1/5-2/A1-1 activated the gene expression of NtANS and NtDFR in tobacco. Our results suggested that low temperature storage could stimulate the anthocyanin accumulation in harvested kiwifruit via regulating several structural and regulatory genes involved in anthocyanin biosynthesis.